Eksplorasi Pengetahuan lokal Etnomedisin Daun katuk (Sauropus AndÃogynus (L.)MeeÃ) Booster ASI pada Ibu Menyusui di Kelurahan Sampara Kabupaten Konawe - Mien, Mien; Hasrima, Hasrima; Narmi, Narmi (Universitas Batanghari Jambi, 2024)
Providing breast milk (ASI) is very important for optimal growth and development of babies. One of the efforts that can be made to increase breast milk production is with herbs such as katuk extract (Sauropus androgynus (L.) Merr.) Knowledge about the use of plants as medicinal ingredients used in various ethnic groups in Indonesia has not been utilized properly. Ethnomedicine studies are a scientific way to document the use of plants as medicinal ingredients in various tribes. The aim of this research is to find out the form of the herb, how to process it, how to use it and the factors behind people using katuk leaves (Sauropus androgynus (L.) Merr) as a breast milk booster in the Sampara sub-district. The research method used was qualitative descriptive observational. The sampling technique is purposive sampling through observation and in-depth interviews with informants. The results of the research showed that participants said that the shape of the katuk leaf concoction was made like a clear vegetable with leaves shaped like Moringa, they did not know the taste of katuk leaves, received support and the cooking method used by the participants stated that before boiling, boil water, wash katuk leaves, add flavoring, then cooked for 3-5 minutes and then consumed during breastfeeding but the problem is that katuk leaves are difficult to buy.